Analysis of Development of Entrepreneurship Competences of Engineering Students Based on EntreComp Framework - Pasic, Mirza; Vatres, Ajdin; Bijelonja, Izet; Pasic, Mugdim (International Journal of Industrial Engineering and Management, 2023)
Engineering graduates play an important role in sustainable development, digital and green transition, and thus entrepreneurship competences. The focus of this research was to assess and compare perceptions of engineering students and professors of students’ entrepreneur- ship competences development through formal learning by attending non-entrepreneurship study programs, as well as to assess the response of the students when they were exposed to informal entrepreneurship learning. Research data were collected using online question- naires based on the EntreComp framework. Regarding formal learning results of the re- search showed that students thought that the non-entrepreneurship courses they attended helped them to develop certain entrepreneurship competences. Entrepreneurship compe- tences didn ́t improve during the first year of the master’s study program, and there was an improvement in some competences during the third year of the bachelor study program. This research showed that it was important to pay attention to informal entrepreneurship learning in the future, for the purpose of entrepreneurship competences development since students expressed a high level of satisfaction with such kind of learning. Article history: Received (December 31, 2022); Revised (April 28 2023); Accepted (May 9, 2023); Published online (May 22, 2023)